2013
DOI: 10.5037/jomr.2013.4205
|View full text |Cite
|
Sign up to set email alerts
|

Maxillomandibular Advancement in Obstructive Sleep Apnea Syndrome Patients: a Restrospective Study on the Sagittal Cephalometric Variables

Abstract: ObjectivesThe present retrospective study analyzes sagittal cephalometric changes in patients affected by obstructive sleep apnea syndrome submitted to maxillomandubular advancement.Material and Methods15 adult sleep apnea syndrome (OSAS) patients diagnosed by polysomnography (PSG) and treated with maxillomandubular advancement (MMA) were included in this study. Pre- (T1) and postsurgical (T2) PSG studies assessing the apnea/hypopnea index (AHI) and the lowest oxygen saturation (LSAT) level were compared. Late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 32 publications
0
58
0
4
Order By: Relevance
“…In general, maxillomandibular retrusion tends to markedly decrease the pharyngeal airway space (PAS). Several studies have reported that MMA surgery is effective for improving the PAS in such patients [2,3]. Genioplasty surgery, including MMA, is also believed to increase PAS by promoting muscle changes [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In general, maxillomandibular retrusion tends to markedly decrease the pharyngeal airway space (PAS). Several studies have reported that MMA surgery is effective for improving the PAS in such patients [2,3]. Genioplasty surgery, including MMA, is also believed to increase PAS by promoting muscle changes [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…DISE is not yet routinely performed prior to MMA, as opposed to awake lateral cephalograms. 31,[38][39][40] However, cephalometry has several important limitations when applied to the upper airway, resulting in conflicting reports. 8,41 Some studies show no predictive value of specific cephalometric parameters, whereas others do link some parameters to success.…”
Section: Discussionmentioning
confidence: 99%
“…10 Studies have found that MMA is an effective surgical treatment for moderate and severe OSA, especially when patients present with a retro positioned maxillomandibular complex 19,23,24 . These studies have included patients with AHIs greater than 15.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…technique for treatment of moderate to severe OSA 16,[19][20][21][22][23][24] . MMA surgery increases the…”
Section: Maxillomandibular Advancement Surgery (Mma) Is An Effectivementioning
confidence: 99%